1985
DOI: 10.1172/jci111814
|View full text |Cite
|
Sign up to set email alerts
|

Platelet antibodies of the IgM class in immune thrombocytopenic purpura.

Abstract: The clinical course and response to therapy of patients with immune thrombocytopenic purpura (ITP) are not completely determined by the level of IgG present on the platelet surface. It is possible that antibodies of other immunoglobulin classes also play a role in platelet destruction in some of these patients. Therefore, we studied 175 patients with ITP for the presence of IgM anti-platelet antibodies using radiolabeled polyclonal or monoclonal anti-IgM. We observed that 57% of patients with clinical ITP had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…IgM‐associated PLT activation and clearance have been reported in several disorders including immune thrombocytopenia, 32‐35 multiple sclerosis, 36 dengue viral infection, 37 and other infectious diseases 38 . Immune complexes binding to PLT Fc receptors have also been demonstrated in ITP, septicemia, and pediatric infectious diseases 38,39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgM‐associated PLT activation and clearance have been reported in several disorders including immune thrombocytopenia, 32‐35 multiple sclerosis, 36 dengue viral infection, 37 and other infectious diseases 38 . Immune complexes binding to PLT Fc receptors have also been demonstrated in ITP, septicemia, and pediatric infectious diseases 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has suggested that several PLT glycoproteins, such as GP IIb/IIIa, GP Ib, and GP V, act as target antigen sites for the attachment of these immune complexes as well 34,39,40 . Consequently, this binding activates complement system which contributes to PLT activation and clearance 32,41‐43 . Upon activation, PLTs change their spherical shape, release granule contents, aggregate, activate the coagulation process, and initiate the fibrin clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…Most autoantibodies found in chronic ITP patients are of the IgG class, but IgM and sporadically IgA antibodies are also detected ( 100 102 ). IgM antibodies were shown to fix complement on platelets which could facilitate clearance, but this has not been further investigated; IgG autoantibodies seem to be the main mediator of antibody-driven autoimmunity ( 100 ).…”
Section: Etiologymentioning
confidence: 99%
“…Most autoantibodies found in chronic ITP patients are of the IgG class, but IgM and sporadically IgA antibodies are also detected ( 100 102 ). IgM antibodies were shown to fix complement on platelets which could facilitate clearance, but this has not been further investigated; IgG autoantibodies seem to be the main mediator of antibody-driven autoimmunity ( 100 ). Most prevalent are IgGs of the IgG1 subclass, and while IgG2, IgG3, and IgG4 subclass autoantibodies can be also found in patients, they are often accompanied by IgG1 antibodies ( 103 , 104 ).…”
Section: Etiologymentioning
confidence: 99%
“…The mechanism of thrombocytopenia in ITP is considered to be due to increased platelet destruction by anti-platelet autoantibodies, mainly anti-GPIIb-IIIa and/or anti-GPIb-IX antibodies (12,17). The autoantibodies reported most have belonged to the IgG class, and little is known about IgM autoantibodies except a few reports of elevated levels of PAIgM in ITP patients (18,19). We have reported immune-mediated cyclic thrombocytopenia caused by IgM anti-GPIIbIIIa autoantibodies (20) and, in the present paper, we have shown that elevated PAIgM is due to 'anti-platelet autoantibodies' in most of the ITP patients.…”
Section: Anti-hcv Antibodies In Palgg or Palgmmentioning
confidence: 99%